Overuse in the criminal justice system: on criminalization, prosecution and imprisonment = Le recours excessif au système de justice pénale : aux sanctions et poursuites pénales et à la détention - Kempen, P. H. P. H. M. C. van (Publication, 2019)
The criminal justice system encompasses the most severe instrument at the state?s disposal in times of peace. For this and many other reasons, overuse of that system is a serious matter.00It may present itself in different forms. Overuse of criminalization may mean that too much conduct is criminalized without necessity. Overuse of prosecution may present itself if too many violations of criminal offences are prosecuted, while in certain individual cases or specific categories of cases it would be more effective, fairer, more efficient or otherwise desirable to refrain from prosecution and/or to apply alternative means, such as negotiating justice or administrative fines. Finally, the criminal justice system can be overused through the application and execution of too many or too severe prison sentences.00All these forms of overuse are discussed in this volume. It contains one introductory chapter, seven thematic chapters and sixteen chapters on individual countries around the world. Themes discussed in these chapters are, among others, the principle that criminal law is and must be regarded as a so-called ultima ratio or ultimum remedium, the relevant human rights framework, worldwide statistics, and legal and practical restraints as well as possibilities to solve overuse.00Containing an extensive collection of expert knowledge, this volume intends to expose legal possibilities, good practices and the many challenges that lie ahead when attempting to prevent overuse in the criminal justice system